ChemInform Abstract: Frame‐Guided Assembly of Amphiphiles. Issue 8 (February 2016) - Dong, Yuanchen; Liu, Dongsheng
Abstract: Review: principles, basic requirements, prospects and potential investigations of frame‐guided assembly; 21 refs.